KOMUNITAS K-POPERS PEKANBARU (STUDI TENTANG PEMBENTUKAN KELOMPOK SOSIAL) - Eriska Rena; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Globalization brought the Korean Wave virus into Pekanbaru and caused emergences many Korean culture lovers, especially among young people. This also raises awareness by some young people to establish a community called Komunitas K-Popers Pekanbaru which aims as a forum for gathering of fans and a place to train the talents of its members. This study aims to determine the factors of community formation and social interaction processes that occur both between members and with other communities. The research method used qualitative research because the topic is difficult to be measured by data collection techniques through interviews, observation and online data tracking. Informant consists of 5 permanent members of the selected community using purposive sampling technique by meeting several criteria determined by the researcher. Through this research, it is concluded that the formation of K-Popers Pekanbaru Community because of the similarity of interest in K-Pop culture, as a media for sharing and exchanging information also to become a place for K-Popers to practice and develop their dance cover hobby . The social interaction that occurs in this community arises after the fulfillment of social interaction requirement that is social contact that most of them done indirectly by using TV and internet media and social communication which aims to convey messages and information relating to K-Pop.Keyword: Social groups, communities, social interactions, k-popers